2020
DOI: 10.11113/umran2020.7n1.364
|View full text |Cite
|
Sign up to set email alerts
|

Terrorist Deradicalization Programs in Saudi, Yemen and Malaysia

Abstract: Terrorist Deradicalization is advancing subject of scientific study that lacks universally accepted definition. It is presently understood as efforts that attempt transform attitudes and behaviors of former terrorists so they reject violence as a tool to achieve ideological, religious or political goals that threaten national security and life or cause political and economic instability. Saudi Arabia Yemen and Malaysiahave deradicalization programs called Al-Ha’ir, Al-Hitar and Pemulihan, respectively, that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The study of recidivism of US terrorism-related offenders shows that there are possibilities that a terrorist is will repeat an offence related to terrorism (Hodwitz, 2019). Reintegration throughout the process of the Patriot Act has always been a challenge and commonly discussed in literature (Hagan et al, 2009;Aslama and Bakarb, 2019;Hodwitz, 2019).…”
Section: Criminal Justicementioning
confidence: 99%
See 2 more Smart Citations
“…The study of recidivism of US terrorism-related offenders shows that there are possibilities that a terrorist is will repeat an offence related to terrorism (Hodwitz, 2019). Reintegration throughout the process of the Patriot Act has always been a challenge and commonly discussed in literature (Hagan et al, 2009;Aslama and Bakarb, 2019;Hodwitz, 2019).…”
Section: Criminal Justicementioning
confidence: 99%
“…The Malaysian prison department provides security and humane treatment to detainees throughout the implementation of specific rehabilitation programmes (Hamidi, 2016; Tan, 2019). Previous studies on the Security Offences (Special Measures) Act 2012 (SOSMA) and Prevention of Terrorism Act 2015 (POTA) offenders indicated that one of the main factors they are involved in such acts are due to influence of radicalism, different levels of ideologies, substantial rewards for their actions spiritually or financially and influence from their colleagues (Aslam et al , 2016; Aslam, 2017; Aslama and Bakarb, 2019). The Royal Malaysia Police (RMP) also provides many training programmes, financial assistance and moral support for ex-detainees, ex-prisoners (ex-terrorists) and their family members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation